Influence of Salix babylonica extract, exogenous enzyme of xylanase and their combination on blood haematological and biochemical profile in sheep and goats - RIVERO, N; SALEM, A Z M; AYALA, M; ELGHANDOUR, M M Y; KHOLIF, A E; BARBABOSA, A; CAMACHO, L M; ROJAS, S; JOLIVARES, JOLIVARES; CIPRIANO, M (The Indian Journal of Animal Sciences, 2016)
The study was made to investigate effect of exogenous enzyme of xylanase, Salix babylonica extract and their combination on blood haematological and biochemical profile in lambs and goats. Suffolk lambs (4) and Saanen goats (4) were used in a Latin square design (4 animals × 4 treatments in 4 periods) for 15 days of adaptation. Animals were fed the basal diet plus 30 ml of water (control), or plus 30 ml of exogenous enzyme xylanase (EZ), or plus 30 ml of S. babylonica extract (SB), or plus 30 ml of xylanase + 30 ml of SB extract (EZSB). The daily dose of treatments was given orally before the morning feeding. Blood samples (5 ml) were collected on day 15 of each period and analyzed for haematological and biochemical profile. Treatments had affected hematocrit in lambs; eosinophils and glucose in goats. Since all the studied blood parameters were within the normal range for healthy goats and there were no signs of disease, it is concluded that xylanase, S. babylonica and their combination did not pose any threat to the health of the animals under the conditions of the experiment where both feed additives are innocuous.